2015
DOI: 10.1111/ppe.12225
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Social Support during Pregnancy: a Systematic Review and Meta‐Analysis

Abstract: There is no evidence for a direct association between social support and preterm birth. Social support, however, may provide a buffering mechanism between stress and preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 40 publications
2
48
0
1
Order By: Relevance
“…which included studies from high- and middle-income countries, concluded that there was no significant association between LBW and antenatal social support (pooled OR = 1.22, 95% CI: 0.84–1.76). [ 22 ] However, this meta-analysis did not include studies from low-middle income countries in which the sociodemographic scenario is very different from high-income countries. In low- and middle-income countries, women are more dependent on men for emotional, financial, instrumental, informational support, and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…which included studies from high- and middle-income countries, concluded that there was no significant association between LBW and antenatal social support (pooled OR = 1.22, 95% CI: 0.84–1.76). [ 22 ] However, this meta-analysis did not include studies from low-middle income countries in which the sociodemographic scenario is very different from high-income countries. In low- and middle-income countries, women are more dependent on men for emotional, financial, instrumental, informational support, and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Birth outcomes and pregnancy complications: For example, birth weight; APGAR score; admission to neonatal intensive care unit; intrauterine fetal demise; neonatal death; maternal anthropometric measures; gestational weight gain; pre-eclampsia; gestational hypertension; gestational diabetes; intrauterine growth restriction; macrosomia (birth weight > 4000 g); hospital admission during pregnancy and the reason; mode of delivery; induction and reason.Maternal psychosocial measures: For example, a) Patient Activation Measure (13 items assessing confidence, knowledge, and skills in managing health and healthcare); b) Coping Inventory (15 items reflecting a range of coping strategies to manage preparing for a baby, adapted from established coping scales with additional items developed through focus groups and pilot testing with pregnant women) [43]; c) Prenatal Distress Questionnaire (a17-item scale assesses common worries and stressors during pregnancy, including concerns about labor and delivery, paying for the baby’s expenses, and managing work, relationships, and childcare) [44]; d) Perceived Stress Scale (a generalized measure assessing how overwhelmed people feel about their life circumstances [45, 46]; e) Stress Management Practices subscale of the Health Promoting Lifestyle Profile II [47, 48]; f) Prenatal Anxiety (13 items measures the emotional state of anxiety arising from women’s concerns about their pregnancy) [49]; g) Depression (The Center for Epidemiological Studies Depression Scale) [50]; h) Shift and Persist (14 item scale measures resilience) [51]; i) Everyday Discrimination Scale [52]; j) Discrimination in Prenatal Care (derived from PRAMS, Centers for Disease Control and Prevention, 2014]; k) Adverse Childhood Experience Study questions (adapted from the Behavioral Risk Factor Surveillance System questionnaire 2014 version) [53]; l) Support from Baby’s Father [54]; m) Perceived Family Support [55]; n) Role of religiosity in dealing with stress, and o) Perceived Neighborhood Safety.Maternal behavioral and other measures: for example, maternal smoking, alcohol and marijuana use; pregnancy intention; physical activity, dietary intake and multivitamin use; housing instability, access to healthcare, food insecurity, income, breastfeeding at hospital discharge and postpartum visit.Race/Ethnicity: Identifying the race of participants will be our most important quantitative measure. Indeed, the epidemiologic literature suggests that the categories of race and ethnicity reflect distinct social and environmental influences rather than actual genetic variations between populations [56–59].…”
Section: Methodsmentioning
confidence: 99%
“…Maternal psychosocial measures: For example, a) Patient Activation Measure (13 items assessing confidence, knowledge, and skills in managing health and healthcare); b) Coping Inventory (15 items reflecting a range of coping strategies to manage preparing for a baby, adapted from established coping scales with additional items developed through focus groups and pilot testing with pregnant women) [43]; c) Prenatal Distress Questionnaire (a17-item scale assesses common worries and stressors during pregnancy, including concerns about labor and delivery, paying for the baby’s expenses, and managing work, relationships, and childcare) [44]; d) Perceived Stress Scale (a generalized measure assessing how overwhelmed people feel about their life circumstances [45, 46]; e) Stress Management Practices subscale of the Health Promoting Lifestyle Profile II [47, 48]; f) Prenatal Anxiety (13 items measures the emotional state of anxiety arising from women’s concerns about their pregnancy) [49]; g) Depression (The Center for Epidemiological Studies Depression Scale) [50]; h) Shift and Persist (14 item scale measures resilience) [51]; i) Everyday Discrimination Scale [52]; j) Discrimination in Prenatal Care (derived from PRAMS, Centers for Disease Control and Prevention, 2014]; k) Adverse Childhood Experience Study questions (adapted from the Behavioral Risk Factor Surveillance System questionnaire 2014 version) [53]; l) Support from Baby’s Father [54]; m) Perceived Family Support [55]; n) Role of religiosity in dealing with stress, and o) Perceived Neighborhood Safety.…”
Section: Methodsmentioning
confidence: 99%
“…Studies done by Wado et al and a meta-analysis done by Hetherington et al showed that higher perceived social support is negatively associated with LBW. 16,17 But, study done by Almeida et al found that low social support was a negatively associated with LBW. 15 This difference in results might be due to difference in study setting and the study tool used.…”
Section: Social Support and Low Birth Weightmentioning
confidence: 99%